Methodological and conceptual issues regarding occupational psychosocial coronary heart disease epidemiology - Hermann Burr; Maren Formazin; Anne Pohrt (Nordic Association of Occupational Safety and Health (NOROSH), 2016)
Overview Psychosocial occupational epidemiology has mainly focused on the demand-control and, to a much lesser extent, the effort-reward-imbalance (ERI) models. These models and the strong focus on them raise some conceptual and methodological issues we will address in the following letter. The conceptual issues include the empirical confirmation of the assumptions of these models, the extent to which the focus on the demand-control and ERI models is warranted, and whether the sub-dimensions of the scales in these models have common health effects. We argue that there is a lack of empirical approval of (i) the assumptions behind both models and (ii) the focus on these models. The methodological issues include how exposure to job strain is categorized, how ERI previously has been measured, and the validity of self-reports of job strain. We argue that (i) a population independent definition of job strain is lacking, (ii) the older measurements of ERI mix exposure and effect, and (iii) we know little regarding the validity of the measurement of the psychosocial working environment. Finally, we suggest that analyses of monitoring data with a broader focus on the psychosocial working environment can be used to shed light to some of the issues raised above. Introduction In the last three decades (1, 2), psychosocial occupational epidemiology related to coronary heart disease (CHD) has mainly focused on the job-strain model, also referred to as the demand-control model (3, 4). In this model, two aspects of work are deemed relevant: demands and control. Negative consequences to health are to be expected when high demands are simultaneously present with low control. This combination has been termed job strain (3, 4). Recently, there has also been increased interest in the ERI model (5, 6) which considers the level of effort relative to rewards at work: an imbalance is present when the efforts outweigh the rewards (5, 6). In longitudinal studies of CHD, there has been only a limited focus on investigating occupational psychosocial factors outside of these two models (1, 2). In this letter, we would like to raise some conceptual and methodological issues which are inherent to these two stress models but also which arise from the heavy emphasis placed on them. Conceptual issues The conceptual issues we discuss below are empirical confirmation of the assumptions of these models and to what extent the focus on the demand-control and ERI models is warranted. Investigating the assumptions of the models Both the demand-control and the ERI models are based on assumptions which have only been tested empirically to a limited extent (1, 2). We pose three specific questions: (i) Does the interaction of demands and control constitute a risk factor for CHD? (ii) Does the imbalance between effort and reward explain more variance in CHD risk than high effort and low reward alone? (iii) Do the sub-dimensions of the scales in these models have common health effects? Regarding the interaction of demands and control. The concept of the demand-control model is useful when the health risk of being exposed to job strain (simultaneous high demands and low control) differs greatly from the sum of individual health risks of being exposed solely to high demands and low control. If this interaction were not present, it would be warranted to look separately at high demands and low control. This would for instance counteract overlooking those persons exposed to low control but not high demands (known as "passive work"; 3, 4). It should be emphasized that the interaction of demands and control has only been tested in very few - underpowered - cases (1, 2). Initial support for an interaction within the demand-control model can be tentatively derived from the work of the IPD-Work Consortium (7): In a reanalysis of an earlier study (8), it was shown that while neither demands nor job control alone (appendix to 8) predicted CHD, job strain did when controlling for sex, age and socioeconomic status (SES) (9). This indicates that an interaction takes place. Controlling for SES is of high relevance - otherwise, the results point in a different direction (10). However, a formal test of interaction was not performed on the IPD-Work Consortium data. Even the IPD study itself might not have sufficient statistical power to analyze a possible interaction directly: this requires many more observations than simply looking at the main effects (2). If one is interested in investigating an interaction, more incident outcomes are often required (11). Regarding effort-reward imbalance. Similarly to the combined effect of demands and control described above, focusing on the ERI model makes sense only if the imbalance of effort and reward explains the risk of CHD over and above the effect of high efforts and low rewards. To our knowledge, this has not been verified in any longitudinal study of CHD (1, 2). Regarding the effect of sub-dimensions. Finally, using the scales of the two models (demands and control or efforts and rewards) is meaningful only if the sub-dimensions of the scales all have about equal effect sizes and signs. For example, the scale psychological demands covers the sub-dimensions work pace, role conflict and work amount while control covers both influence (decision authority) and opportunities for development (skill discretion). Do these dimensions predict the risk of CHD to equal amounts within their respective scales? For now, this has not been tested elaborately to our knowledge (1, 2, 12). Consequently, it is possible that certain risk factors in the psychosocial work environment may be overlooked due to different risk factors being merged into one scale. Is the focus on the demand-control and ERI models warranted? In the past, longitudinal epidemiological research on psychosocial work characteristics and their association with the risk of CHD has mainly focused on the demand-control and - to a much lesser extent - ERI models (1). For example, in a recent review (2) covering 44 papers and including 170 analyses, 70% percent of those dealt with these models or sub-dimensions thereof. Interestingly, the demand-control model alone accounted for 66% of the analyses and ERI only 4%. A further 11% of the analyses dealt with working hours, 9% with social support, 5% with job insecurity, 3% with leadership and the remaining 3% covered conflicts, justice or predictability. Maintaining the currently high degree of focus on the DC and ERI models requires evidence that job strain and ERI are by far the most important risk factors for CHD. The review by Pejtersen et al (2) has additionally pointed out that of the 44 studies mentioned above, only two - an IPD-Work Consortium study (8) and a Swedish case-control study (13) - contained analyses with sufficient statistical power to detect an elevated CHD risk of 20%. These two sufficiently powered studies available as of April 2013 have led to the following conclusions: (i) job strain was found to be predictive of CHD in the IPD-Work Consortium study (8); and (ii) both low control and low social support predicted CHD in the Swedish study (13). Recently, a well-powered study on working hours (14) indicated that long working hours constitute a risk factor for CHD. Additionally, a recently published large study on job insecurity (15) is worth mentioning. While there was not sufficient power to detect a 20% increased risk due the relatively low prevalence of job insecurity, the study did have sufficient power to find a risk of 1.32 - which is the value actually found empirically (15). Summarizing the small number of well-powered studies available at this time indicates that both model dimensions (job strain) as well as non-model dimensions (social support and working hours) predict CHD (8, 13-15). In this context, one should bear in mind that the variety of possible dimensions that can be considered as constituting "psychosocial work environment" is large. The latter is exemplified by a recent analysis of the psychosocial content of seven European work environment monitoring questionnaires which showed that there are 34 distinct dimensions of the psychosocial work environment (16). Around half of these dimensions are not found in either the demand-control or ERI models (16).